Peningkatan Hasil Belajar Pancasila Menggunakan Model Pembelajaran Tipe STAD Berbantuan Canva di Kelas V SDN 03 Gunung Tuleh - Aisah, Siti; Putera, Rafhi Febryan; Rahmatina, Rahmatina; Ladiva, Hasmai Bungsu (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to improve the learning outcomes of Pancasila education using the STAD cooperative learning model assisted by Canva in class V SDN 03 Gunung Tuleh. The type of research used is Classroom Action Research with stages of planning, implementation, observation, and reflection. The subjects in this study are teachers and students of class V SDN 03 Gunung Tuleh with a total of 18 students. Data were collected through test and non-test techniques, while the research instruments included observation sheets for teaching modules, observations of teachers, and students. The research results show that the use of the STAD cooperative learning model assisted by Canva can significantly improve the learning outcomes of Pancasila education. In the first cycle, the average score for the teaching module aspect was 85.4% with a qualification of (B), increasing in the second cycle to 95.8% with a qualification of (SB). The implementation results of the teacher and students' aspects in the first cycle obtained the same score with an average of 86.75% qualification (B), increasing in the second cycle to 93.7% qualification (SB). The students' learning outcomes in the first cycle had an average of 69.1 qualification (D), increasing in the second cycle to 87.22 qualification (B). Therefore, the application of the STAD cooperative model assisted by Canva can improve the learning outcomes of students and is suitable to be used in teaching Pancasila Education for grade V at SDN 03 Gunung Tuleh.